(3aJfI GdLed jhe GdHUQI hCMcGe GdeJhdjf ddbJGds - (3GdYcHQj, GdMGQKj, GdHZOGOj, GdcQNj, CHh YHO Gddg, GdTjN GdoepajO, eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe, J (B413s ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3GdGNJdGa Hjf Cgd GdbHdI aj MOjK GdaJfI HGdHUQI heG cGf Hjf CejQ GeDefjf Ydj Hf CHj WGdH Ydjg GdSdGe hHjf YGFTI hWdMI hGdRHjQ ef GdMQH GdeghdI hGdbJGd hePgH cd aQjb ef GdCeI ajg Ydi TQM dg (B...s
(3BNQgG (B:s
... (3Ke bGe NWjHG aMeO Gddg hCKfi Ydjg CeG HYO aEf Gddg deG bHV fHjg Udi Gddg Ydjg hBdg bdfG fMf Cgd HjJg hYUHJg hhQKJg hChdjGFg hCMb Ndb Gddg Hg (B..(3aQZJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\21s
(3GdCYdGe (B8\300s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds